Estudos fitogeográficos e modelagem ecológica do gênero Dimorphandra Schott (Leguminosae, Caesalpinioideae) - Matos, Rafael Pereira de (2015)
Studying patterns of distribution of organisms is relevant in ecology, biogeography and conservation studies under even to understand the evolution of biodiversity. Dimorphandra Schott. is a widespread neotropical genus with 25 taxa in Brazil, occurring in savanna (Cerrado) and ombrophylous vegetation (Amazonia and Atlantic Rain Forest). This work aims to understand the factor that drives the richness and diversity of Dimorphandra. We used SIG, ecological modeling and databank of SpeciesLink and bibliography. These data were classified within biogeographic provinces according to a biogeographically regionalization scheme and according to groups generated by a cluster analysis in the PC-ORD program and a Parsimony Analysis of Endemicity (PAE) by PAUP program. At the same time, ecological distribution models were formulated to the past, present and future based on algorithms (BIOCLIM and CCSM) using the softwares MAXENT and DIVA-GIS, referring to each group according to the UPGMA results. The richness and diversity centers were in the Amazon region. The species more widespread were D. mollis Benth. and D. gardneriana Tul., occurring in the Seasonal Tropical Dry Forests (STDFs) in the northeast-southeast direction. Three phytogeographic groups were determined by the cluster analysis: A) Amazon and its two subgroups: Broad Amazon and North of Negro River Basin; B) Ecotones Brazilian Savanna/Atlantic Forest; and C) Guyana Highlands. PAE analysis pointed two major clades with good support (>80% bootstrap). Some distribution patterns were determined: 1) Broad Amazon Pattern, 2) Restricted to northern Amazon Pattern, 3) Guyana Shield Pattern, 4) Ecotones Brazilian Savanna/Atlantic Forest Pattern and 5) Micro Endemic Minas Gerais’ Brazilian Savanna Pattern. Predictive modeling results demonstrated a trend on reduction of most potential occurrence areas, except in small regions in Guyana Highlands, which expanded in a future scenario. Finally, we can conclude that distribution of the genus through South America was known as well its richness and diversity centers, besides it has been checked a general trend on reduction of potential occurrence area of this genus in a future scenario except in high areas which are considered refugia.